2021
DOI: 10.1002/ijc.33453
|View full text |Cite
|
Sign up to set email alerts
|

Trilaciclib prior to chemotherapy and atezolizumab in patients with newly diagnosed extensive‐stage small cell lung cancer: A multicentre, randomised, double‐blind, placebo‐controlled Phase II trial

Abstract: Trilaciclib is an intravenous CDK4/6 inhibitor administered prior to chemotherapy to preserve haematopoietic stem and progenitor cells and immune system function from chemotherapy‐induced damage (myelopreservation). The effects of administering trilaciclib prior to carboplatin, etoposide and atezolizumab (E/P/A) were evaluated in a randomised, double‐blind, placebo‐controlled Phase II study in patients with newly diagnosed extensive‐stage small cell lung cancer (ES‐SCLC) (NCT03041311). The primary endpoints we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 54 publications
8
80
0
Order By: Relevance
“…In this analysis, patients who received trilaciclib prior to chemotherapy appeared three times less likely to require chemotherapy dose reductions than patients who received placebo, and they had numerically higher RDIs of etoposide and carboplatin. Consistent with findings from the individual studies, [20][21][22] maintaining the dose intensity of chemotherapy did not translate to an improvement in PFS or OS. This is perhaps not surprising, as studies in patients with SCLC have shown that increasing the RDI of chemotherapy beyond the SoC rarely translates into significant improvements in response rates or survival.…”
Section: Clinical Lung Cancer 2021supporting
confidence: 76%
See 2 more Smart Citations
“…In this analysis, patients who received trilaciclib prior to chemotherapy appeared three times less likely to require chemotherapy dose reductions than patients who received placebo, and they had numerically higher RDIs of etoposide and carboplatin. Consistent with findings from the individual studies, [20][21][22] maintaining the dose intensity of chemotherapy did not translate to an improvement in PFS or OS. This is perhaps not surprising, as studies in patients with SCLC have shown that increasing the RDI of chemotherapy beyond the SoC rarely translates into significant improvements in response rates or survival.…”
Section: Clinical Lung Cancer 2021supporting
confidence: 76%
“…The G1T28-05 study was performed to confirm the myeloprotective benefits of trilaciclib in patients receiving E/P/A for the treatment of ES-SCLC. 21 Finally, the supportive G1T28-03 study was performed to investigate the administration of trilaciclib prior to topotecan, a chemotherapy regimen that is more myelosuppressive than E/P, in the second-/third-line setting. 22 All three studies demonstrated a clear multilineage myeloprotection benefit through clinically meaningful reductions in multiple measures of CIM and the need for supportive care interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these positive results in SCLC, a phase 2 study in 102 randomized TNBC patients treated with gemcitabine/carboplatin revealed that trilaciclib administration did not prevent myelosuppression in this patient population; however, improvements in PFS and OS were observed in the trilaciclib group [120,121]. Across the SCLC trials, trilaciclib appeared to be fairly well-tolerated with no reports of bone pain and fewer grade 3 or higher adverse events than placebo-treated groups, primarily due to fewer hematologic toxicities [117][118][119]122] Trilaciclib was approved the US. FDA in February 2021 to reduce the incidence of chemotherapy-induced myelosuppression in adult patients when administered prior to a platinum/etoposide-containing regimen or topotecancontaining regimen for extensive-stage SCLC [123].…”
Section: Trilaciclib: G1 Therapeutics Incmentioning
confidence: 99%
“…Phase 2 randomized, placebo-controlled clinical studies in extensive-stage small cell lung cancer (SCLC) revealed that trilaciclib administration prior to chemotherapy significantly reduced the duration of severe neutropenia in cycle 1 and the occurrence of severe neutropenia during carboplatin/etoposide, carboplatin/etoposide/atezolizumab, or topotecan treatment (77, 107 and 61 randomized patients, respectively). Improvements in red blood cell and platelet counts, and health-related quality-of-life were also observed [117][118][119]. Despite these positive results in SCLC, a phase 2 study in 102 randomized TNBC patients treated with gemcitabine/carboplatin revealed that trilaciclib administration did not prevent myelosuppression in this patient population; however, improvements in PFS and OS were observed in the trilaciclib group [120,121].…”
Section: Trilaciclib: G1 Therapeutics Incmentioning
confidence: 99%